Effect of Spondias mombin leaves' extracts on chemically induced tumor - Olufunke Akanji; Macdonald Idu; Idowu Omotuyi (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: A tumor is merely a mass of tissue that does not perform any physiological function; it can be either benign or malignant. Cancer is being regarded as a malignant ailment emerging from unrestricted cell division occurring in the body to make mass of tissues. Spondias mombin L. (Family- Anacardiaceae) grows in coastal areas and in the rain forest into a big tree of up to 15 - 22 m. This study investigated the efficacy of S. mombin aqueous and n-hexane extracts in chemically induced tumor-bearing animals. Experimental: Twenty-eight (28) healthy rats were used and grouped into seven (7). Six groups were induced with trichloroacetic acid and ethidium bromide leaving out normal control group for 28 days prior to treatments. LBH589 (standard anticancer drug, 500 mg/kg) served as positive control. At the termination of the experiments, the animals were sacrificed; solid tumor volume was determined, blood and tissue samples were collected for hematology and histopathology respectively. Results: The results showed very significant reduction in the solid tumour volumes of S. mombin leaves extracts treated groups compared to positive and untreated control groups. The result of hematological parameters showed that the hemoglobin content, red blood cell and white blood cell counts of all treated groups were near to normal control group. Normal histological features were observed in control group animals, the negative groups showed the manifestations of cancer, all the treatment groups showed significant levels of repair almost similar to normal features in control group particularly in intestines and lungs of the experimental animals. Recommended applications/industries: The present data provided substantial evidence that S. mombin leaves suppressed tumor growth in experimental animals and suggested that the extracts are potential antitumorigenic agent inhibiting chemically induced lung and intestinal tumors.